2005
DOI: 10.1093/jac/dki198
|View full text |Cite
|
Sign up to set email alerts
|

Telavancin: in vitro activity against staphylococci in a biofilm model

Abstract: Telavancin exhibited substantial antimicrobial activity against staphylococcal biofilms, including GISA strains. This study supports the case for the evaluation of telavancin in the treatment of staphylococcal biofilm-associated infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 28 publications
5
47
0
1
Order By: Relevance
“…This multifunctional mechanism of action may help to minimize the potential for the selection of resistance (16,27). In several studies, telavancin has exhibited in vitro activity superior to that of vancomycin (12,15,20,26,33).…”
mentioning
confidence: 99%
“…This multifunctional mechanism of action may help to minimize the potential for the selection of resistance (16,27). In several studies, telavancin has exhibited in vitro activity superior to that of vancomycin (12,15,20,26,33).…”
mentioning
confidence: 99%
“…Efficacy in such infections requires the antibiotic to be active against biofilm-embedded bacteria. In an in vitro biofilim Sorbarod infection model, telavancin was demonstrated to be more active than linezolid, vancomycin and teicoplanin against S. aureus (MSSA, MRSA, coagulase-negative staphylococci and GISA) [35].…”
Section: Rabbit Device Infection Modelmentioning
confidence: 99%
“…Concentration-dependent bactericidal effects were demonstrated in time-kill studies against target organisms, including methicillin-sensitive S. aureus (MSSA), MRSA, VISA and coagulase-negative staphylococci. Telavancin has been shown to retain bactericidal activity against slowly growing isolates of S. aureus in time-kill assays and in in vitro models of biofilm infection [34][35][36][37]. In a model of intracellular S. aureus infection, telavancin therapy resulted in >90% reduction in bacterial titers [38].…”
Section: Bactericidal Activitymentioning
confidence: 99%
“…Animal models evaluating TLV against biofilm-producing S. aureus (and the glycopeptideintermediate Staphylococcus aureus strain), S. epidermidis and Enterococcus faecalis revealed that TLV performed better than glycopeptides (VAN and teicoplanin) and linezolid, with MICs for TLV 8-16 times lower than VAN [Gander et al 2005;Chan et al 2015].…”
Section: Pharmacokinetics/pharmacodynamicsmentioning
confidence: 99%